2000
DOI: 10.1007/s004670000326
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron dextran and erythropoietin use in pediatric hemodialysis patients

Abstract: Recombinant human erythropoietin (rHuEPO) is an effective treatment for the anemia of chronic renal failure. However, adequate availability of iron is necessary for an optimal response. We prospectively evaluated the effect of an intravenous iron protocol in a pediatric hemodialysis unit. Patients with either a serum ferritin less than 150 ng/ml or transferrin saturation (TSAT) less than 20% received intravenous iron dextran during ten consecutive dialysis sessions. The administration of rHuEPO was adjusted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…Twelve (3.2%) of the identified studies met initial criteria for inclusion [4,7,11,12,13,14,15,16,17,18,19,20 ]. Two of these reports [19,20] were excluded because they were preliminary reports of a published study [11], as confirmed by the author (L. Greenbaum, personal communication, 24 April 2002). Another report was excluded because it did not contain specific numerical data for meta-analysis [15].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Twelve (3.2%) of the identified studies met initial criteria for inclusion [4,7,11,12,13,14,15,16,17,18,19,20 ]. Two of these reports [19,20] were excluded because they were preliminary reports of a published study [11], as confirmed by the author (L. Greenbaum, personal communication, 24 April 2002). Another report was excluded because it did not contain specific numerical data for meta-analysis [15].…”
Section: Resultsmentioning
confidence: 97%
“…In three studies [7,11,12] we analyzed results from the entire data set that was published, in order to determine additional results or exclude non-qualifying subjects. Using statistical software (NCSS 2001, NCSS, Kaysville, Utah, USA), we recalculated the mean and standard deviation for included patients.…”
Section: Methodsmentioning
confidence: 99%
“…En resumen, el uso rutinario de una gran cantidad de medicamentos vía oral, sumado a la falta de efectividad de las presentaciones orales de hierro y la actual disponibilidad de preparados intravenosos que se han asociado con una menor frecuencia de eventos adversos, ha determinado, en los últimos años, la realización de un mayor número de estudios respecto al uso de hierro intravenoso en población pediá-trica [49][50][51] .…”
Section: Hierrounclassified
“…En 2 estudios pediátricos que incluyeron a 33 pacientes en hemodiálisis no se reportaron reacciones adversas 49,60 . Eficacia: En uno de los estudios mencionados se analizó de forma prospectiva la respuesta a diferentes dosis de hierro sacarato en 14 pacientes pediátricos en hemodiálisis.…”
Section: Hierro Sacarato: Venofer®unclassified
See 1 more Smart Citation